Smart Culture in Smart City Policies: A Case of Yogyakarta City - Iqbal, Muhammad (JASSP, 2021)
The concept of developing Smart Cities in Yogyakarta is different from the development of Smart Cities in other cities. The Smart City of Yogyakarta is under the big idea of Smart Culture, divided into two fields, namely Smart Education and Smart Tourism. This big concept was taken because Yogyakarta is very thick with its Culture and is known as an education city and tourism city. The idea of Smart Culture is expected to touch all aspects of the lives of the citizens of Yogyakarta that are inseparable from the six basic principles of developing Smart Cities. This study uses a quantitative approach. Data survey was conducted using a questionnaire to the civil servant in Yogyakarta City. The survey results will be analyzed using SmartPLS 3.0 software. The results of this study are divided into two components, namely Tangible and Intangible Culture. This Smart Culture's primary purpose is to make Tangible and Intangible Culture in Yogyakarta City survive and excel. Smart Culture in the city of Yogyakarta acts as an umbrella that underlies the development and other intelligent programs such as smart education and smart Culture. These two components are revealed to be critical projects that can be included in short and medium-term programs on smart education or smart tourism related to Culture. Other findings show that tangible Culture and intangible Culture have a significant influence on smart Culture development.